Combining Robot-Assisted Gait Training and Non-Invasive Brain Stimulation in Chronic Stroke Patients: A Systematic Review - Bressi, Federica; Cinnera, Alex Martino; Morone, Giovanni; Campagnola, Benedetta; Cricenti, Laura; Santacaterina, Fabio; Miccinilli, Sandra; Zollo, Loredana; Paolucci, Stefano; Di Lazzaro, Vincenzo; Sterzi, Silvia; Bravi, Marco (Frontiers in Neurology, 2022)
Gait impairment is one of the most common disorders of chronic stroke patients, which hugely affect the ability to carry out the activities of daily living and the quality of life. Recently, traditional rehabilitation techniques have been associated with non-invasive brain stimulation (NIBS) techniques, which enhances brain plasticity, with the aim of promoting recovery in chronic stroke patients. NIBS effectiveness in improving gait parameters in chronic stroke patients has been in several studies evaluated. Robotic devices are emerging as promising tools for the treatment of stroke-related disabilities by performing repetitive, intensive, and task-specific treatments and have been proven to be effective for the enhancement of motor recovery in chronic stroke patients. To date, several studies examined the combination of NIBS with robotic assisted gait training, but the effectiveness of this approach is not yet well established. The main purpose of this systematic review is to clarify whether the combination of NIBS and robot assisted gait training may improve walking function in chronic stroke patients. Our systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies eligible for review were identified through PubMed/MEDLINE, Embase, Scopus, and PEDro from inception to March 15, 2021 and the outcomes considered were gait assessments. The studies included a total of 186 chronic stroke patients. All studies specified technical characteristics of robot devices and included tDCS treatment, however with high heterogeneity of protocols. The results have shown a significantly greater improvement in walking capacity principally assessed with 6MWT. Finally, research studies have highlighted a positive effect on walking recovery by combination of robot-assisted gait training with non-invasive brain stimulation. Further future studies should identify the best characteristics of the combined therapeutic protocols.